2009
DOI: 10.1104/pp.109.144709
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of AtRECQ3 Reveals Significant Differences Relative to Other RecQ Helicases

Abstract: Members of the conserved RecQ helicase family are important for the preservation of genomic stability. Multiple RecQ homologs within one organism raise the question of functional specialization. Whereas five different homologs are present in humans, the model plant Arabidopsis (Arabidopsis thaliana) carries seven RecQ homologs in its genome. We performed biochemical analysis of AtRECQ3, expanded upon a previous analysis of AtRECQ2, and compared their properties. Both proteins differ in their domain composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 55 publications
3
22
0
Order By: Relevance
“…Fast rezipping events as seen for AtRECQ2 were never observed. When using AtRECQ3 K64M8 with a mutation in the Walker A motif, no unwinding was detected. AtRECQ3 was also by far not able to unwind the full hairpin.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Fast rezipping events as seen for AtRECQ2 were never observed. When using AtRECQ3 K64M8 with a mutation in the Walker A motif, no unwinding was detected. AtRECQ3 was also by far not able to unwind the full hairpin.…”
Section: Resultsmentioning
confidence: 97%
“…8). For this, we use single-molecule measurements that have in recent years become a valuable complement to X-ray crystallography and classical biochemical methodology in mechanistic investigations of helicases.…”
mentioning
confidence: 99%
“…In Arabidopsis, RecQ2 catalyzes Holliday junction branch migration and replication fork regression, while RecQ3 can not act on intact Holliday junctions thus suggesting that these RecQ helicases perform different functions in the cell (Kobbe et al 2009). Moreover, it was also shown that AtRecQ3 differs in its biochemical properties from all other eukaryotic RecQ helicases characterized so far (Kobbe et al 2009). …”
Section: Discussionmentioning
confidence: 97%
“…Homologs of both proteins have been shown to regress replication forks (Kanagaraj et al, 2006;Machwe et al, 2006;Ralf et al, 2006;Blastyá k et al, 2007;Kobbe et al, 2009). Both single mutant lines showed a high sensitivity to DNA-damaging agents that can cause replication fork stalling.…”
Section: Requirement Of Rad5a For Efficient Homologousmentioning
confidence: 99%
“…The minor reduction of HR efficiency detected with the SSA substrate might well be due to lack of the RECQ4A function during resection in our experimental system. Alternatively, RECQ4A might also be involved in reannealing the single-strand ends because some RecQ helicases have been shown to possess annealing activity (Garcia et al, 2004;Cheok et al, 2005;Sharma et al, 2005;Kobbe et al, 2009;Chen and Brill, 2010).…”
Section: Recq4a Plays Multiple Roles In Hrmentioning
confidence: 99%